Dickkopf-3 in aberrant endothelial secretome triggers renal fibroblast activation and endothelial–mesenchymal transition. Issue 1 (3rd May 2018) - Lipphardt, Mark; Dihazi, Hassan; Jeon, Noo Li; Dadafarin, Sina; Ratliff, Brian B; Rowe, David W; Müller, Gerhard A; Goligorsky, Michael S
ABSTRACT: Background: Our laboratory has previously demonstrated that Sirt1 endo−/− mice show endothelial dysfunction and exaggerated renal fibrosis, whereas mice with silenced endothelial transforming growth factor beta (TGF-β) signaling are resistant to fibrogenic signals. Considering the fact that the only difference between these mutant mice is confined to the vascular endothelium, this indicates that secreted substances contribute to these contrasting responses. Methods: We performed an unbiased proteomic analysis of the secretome of renal microvascular endothelial cells (RMVECs) isolated from these two mutants. We cultured renal fibroblasts and RMVECs and used microfluidic devices for coculturing. Results: Dickkopf-3 (DKK3), a putative ligand of the Wnt/β-catenin pathway, was present exclusively in the fibrogenic secretome. In cultured fibroblasts, DKK3 potently induced myofibroblast activation. In addition, DKK3 antagonized effects of DKK1, a known inhibitor of the Wnt pathway, in conversion of fibroblasts to myofibroblasts. In RMVECs, DKK3 induced endothelial–mesenchymal transition and impaired their angiogenic competence. The inhibition of endothelial outgrowth, enhanced myofibroblast formation and endothelial–mesenchymal transition were confirmed in coculture. In reporter DKK3-eGFP × Col3.6-GFPcyan mice, DKK3 was marginally expressed under basal conditions. Adriamycin-induced nephropathy resulted in upregulation of DKK3 expression in tubular and, to a lesser degree, endothelial compartments. Sulindac sulfide was found to exhibit superior Wnt pathway-suppressive action and decreased DKK3 signals and the extent of renal fibrosis. Conclusions: In conclusion, this unbiased proteomic screen of the profibrogenic endothelial secretome revealed DKK3 acting as an agonist of the Wnt pathway, enhancing formation of myofibroblasts and endothelial–mesenchymal transition and impairing angiogenesis. A potent inhibitor of the Wnt pathway, sulindac sulfide, suppressed nephropathy-induced DKK3 expression and renal fibrosis.